An introduction to applied linguistics : from practice to theory - Davies, Alan, 1931 February 17- (Edinburgh textbooks in applied linguistics., 2007)
This second edition of the foundational textbook An Introduction to Applied Linguistics provides a state-of-the-art account of contemporary applied linguistics. The kinds of language problems of interest to applied linguists are discussed and a distinction drawn between the different research approach taken by theoretical linguists and by applied linguists to what seem to be the same problems. Professor Davies describes a variety of projects which illustrate the interests of the field and highlight the marriage it offers between practical experience and theoretical understanding. The increasing emphasis of applied linguistics on ethicality is linked to the growth of professionalism and to the concern for accountability, manifested in the widening emphasis on critical stances. This, Davies argues, is at its most acute in the tension between giving advice as the outcome of research and taking political action in order to change a situation which, it is claimed, needs ameliorisation. This dilemma is not confined to applied linguistics and may now be endemic in the applied disciplines. The book has been updated throughout and provides an excellent introduction to the problems and issues that arise in the practice of applied linguistics. Key Features Surveys current issues in applied linguistics, including the concept of the Native Speaker and the development of World Englishes Examines the influence of linguistics, cognitive science and philosophy on applied linguistics and makes a contrast with educational linguistics Proposes that a key issue for the profession will increasingly be the tension between advice and action Suggests that applied linguistics is a theorising rather than a theoretical discipline. Feedback on the first edition: 'Alan Davies' introductory text forcefully re-echoes the famous Edinburgh series in applied linguistics, which he contributed to in a major way.' Applied Linguistics 'Every discipline coming of age needs to reflect on its origins, its history, its conflicts, in order to gain a better understanding of its identity and its long term objectives. Alan Davies, one of the founding fathers of applied linguistics, is the ideal person for this soul-searching exercise ... Introduction to Applied Linguistics is obligatory reading for students and researchers in applied linguistics, for language professionals and for anyone interested in the link between linguistics and applied linguistics.' Modern Language Review